L.v. Beethoven's monument in Bonn - Emden, Hermann (engraver):::Creator::::::::::::; Hä̈hnel, Ernst Julius, 1811-1891 (sculptor):::Contributor:::::::::::: (Bonn; Germany; T. Habricht)
Engraving by Hermann Emden of sculptor Ernst Julius Häḧnel's bronze statue of Beethoven that stands on Münsterplatz in Bonn, Germany.